An application study for digesting and renovating an imported production technology by means of I.E. methods - Xu, W.; Shen, Z.Z. (Computers & industrial engineering, 1998)
It is particularly important for the developing countries like China to pay high attention to digest, absorb and renovate the imported production technologies and equipment. This paper presents such a research effort done by the authors and their project team recently. Structural analysis and optimization techniques are applied successively to redesign an imported petrochemical production technology.